2009
DOI: 10.1111/j.1467-8276.2009.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Subjective Valuation of Subsistence Crops: The Case of Traditional Maize in Mexico

Abstract: Shadow prices guide farmers' resource allocations, but for subsistence farmers growing traditional crops, shadow prices may bear little relationship with market prices. We econometrically estimate shadow prices of maize using data from a nationally representative survey of rural households in Mexico. Shadow prices are significantly higher than the market price for traditional but not improved maize varieties. They are particularly high in the indigenous areas of southern and southeastern Mexico, indicating lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 34 publications
2
48
0
1
Order By: Relevance
“…11. Arslan and Taylor (2009) find that, in indigenous regions of Mexico in particular, farmers excessively value traditional maize varieties and persist in producing them despite falling prices in the market. 12.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…11. Arslan and Taylor (2009) find that, in indigenous regions of Mexico in particular, farmers excessively value traditional maize varieties and persist in producing them despite falling prices in the market. 12.…”
Section: Discussionmentioning
confidence: 97%
“…They include transaction costs (proxied by R it , a dummy variable indicating whether a village has only dirt roads); instruments for access to US migration networks (M it ); and ethnicity (IN it , a dummy for whether the household head speaks an indigenous language). Past research finds indigenous status to be significantly and positively related to how households value traditional crops (Arslan & Taylor, 2009) and negatively related to wealth and access to resources (Perales, Benz, & Brush, 2005;Smale et al, 2003). The migration instrument is constructed through predicted values generated from a Poisson regression of the number of migrants in the household on distance to the US border, the state migration rate in 1924, the average state migration rate from 1955-1959, and weighted averages of GDP growth in migrant destination states over the five years preceding each round of the survey.…”
Section: Testing the Inverse Efficiency Hypothesismentioning
confidence: 94%
“…One reason for this is that subsistence producers raise crops partly to produce their own food; hence their agricultural practices are not exclusively market-driven, but reflect the need to reproduce the household (De Janvry, 1981;Eakin, 2006;Isakson, 2009). Some have found that the area under maize production can even increase when maize prices decline, as maize farmers seek to compensate for declining prices by applying their labor more intensively (Dyer et al, 2006;Arslan and Taylor, 2009;Arslan, 2011). 5 Maize continues to be produced when opportunity costs are clearly unfavorable .…”
Section: Declining Maize Productionmentioning
confidence: 99%
“…These systems depend crucially on farmers' preferences, incentives, knowledge, management practices, institutions, and social organization (Bellon, Pham, & Jackson, 1997;Brush, 2004;Zimmerer, 2010). Farmers continue to maintain this diversity-known as de facto conservation-because it provides them with a range of benefits such as adaptation to agro-ecological heterogeneity (Ceccarelli, 1996;di Falco & Chavas, 2009;Worthington, Soleri, Aragon-Cuevas, & Gepts, 2012), ways to manage risk (Cavatassi, Lipper, & Narloch, 2011;di Falco & Chavas, 2009;di Falco & Perrings, 2005), options to obtain more diverse products for consumption and sale (Brush, 1992;Keleman, Hellin, & Flores, 2013;King, 2007), and the provision of marketing opportunities (Devaux et al, 2009;Keleman et al, 2013;King, 2007), not to mention for cultural value (Arslan & Taylor, 2009;Brush, 1992;Isakson, 2011;Perales, Benz, & Brush, 2005;Rana, Garforth, Sthapit, & Jarvis, 2007).…”
Section: Introductionmentioning
confidence: 97%